NaF PET/CT for response assessment of prostate cancer bone metastases treated with single fraction stereotactic ablative body radiotherapy - Nicholas Hardcastle (Radiation Oncology, 2019)
Abstract Introduction In prostate cancer patients, imaging of bone metastases is enhanced through the use of sodium fluoride positron emission tomography (18F-NaF PET/CT). This imaging technique shows areas of enhanced osteoblastic activity and blood flow. In this work, 18F-NaF PET/CT was investigated for response assessment to single fraction stereotactic ablative body radiotherapy (SABR) to bone metastases in prostate cancer patients. Methods Patients with bone metastases in a prospective trial treated with single fraction SABR received a 18F-NaF PET/CT scan prior to and 6 months post-SABR. The SUVmax in the tumour was determined and the difference between before and after SABR determined. The change in uptake in the non-tumour bone was also measured as a function of the received SABR dose. Results Reduction in SUVmax was observed in 29 of 33 lesions 6 months after SABR (mean absolute decrease in SUVmax 17.7, 95% CI 25.8 to − 9.4, p = 0.0001). Of the three lesions with increased SUVmax post-SABR, two were from the same patient and located in the vertebral column. Both were determined to be local progression in addition to one fracture. The third lesion (in a rib) was shown to be controlled locally but suffered from a fracture at 24 months. Progression adjacent to the treated volume was observed in two patients. The non-tumour bone irradiated showed increased loss in uptake with increasing dose, with a median loss in uptake of 23.3% for bone receiving 24 Gy. Conclusion 18F-NaF PET/CT for response assessment of bone metastases to single fraction SABR indicates high rates of reduction of osteoblastic activity in the tumour and non-tumour bone receiving high doses. The occurrence of marginal recurrence indicates use of larger clinical target volumes may be warranted in treatment of bone metastases. Trial registration POPSTAR, ‘Pilot Study of patients with Oligometastases from Prostate cancer treated with STereotactic Ablative Radiotherapy’, Universal Trial Number U1111-1140-7563, Registered 17th April 2013.